Association of Gastro-Esophageal Reflux Disease with Persistent Cough in Infants: Association of Gastro-Esophageal Reflux - Ansari, Sehar; Lodhi, Aysha Mansoor; Anwar, Shah Jahan; Jamil, Sana; Zafar, Bilal (Pakistan Journal of Health Sciences, 2025)
Gastroesophageal reflux disease (GERD) is widely recognized, alongside upper airway cough syndrome (also known as postnasal drip syndrome) and eosinophilic airway inflammation, as one of the predominant causes of chronic cough. Numerous global respiratory societies have published cough management guidelines that advocate for the assessment and treatment of GERD as a fundamental aspect of the diagnostic and therapeutic framework for addressing chronic cough. Objectives: To determine the association of gastroesophageal reflux disease with persistent cough in infants. Methods: This case-control study was conducted in the Department of Paediatric Medicine at The Children’s Hospital and The Institute of Child Health, Lahore, from August 25, 2022, to February 25, 2023. This study was conducted on infants with complaints of persistent cough and healthy controls. These two groups underwent baseline assessment carried out by physicians and a diagnosis of GERD was made through a barium swallow test. The data were analyzed through SPSS version 25.0. Odds ratio (OR) was calculated to measure the association between persistent cough and GERD. Results: Among case patients, the mean age was 2.92±2.17 months, and 3.67±2.41 months among control patients. By comparing GERD between case and control groups, it was found that the percentage of GERD was 17.6% in case children and 5.9% control children. The difference was significant (p=0.033) and the risk ratio (OR=3.429). Conclusions: The presence of gastroesophageal reflux disease exhibited a notable correlation with the occurrence of chronic cough in the infant population.